The private collection: aura, the cult of celebrity and, the construct of value in saleable works of art - Ellis, Yvette Tamsin (Rhodes University, Faculty of Humanities, Department of Fine Art)
A tenet of the twenty-first century is the monetisation of everything due to commercialisation. The effects of this commercialisation have crept into every aspect of our lives, and although in the art world it has mostly been underhanded in its adoption, the traces of commercialisations touch are still evident in its functioning. Due to this underhandedness there hasn't been much thought put into what 'the monetisation of everything' truly implies for the industry, or how the value of the art object devoted to commercialisation may look like. The Private Collection (exhibition title of the practical component for submission in MFA completion) addresses the concept of object value and, more specifically, how that value is created within the art world through mechanisms of commercialisation that include celebrity cult, functioning of possession (through collecting), and taste. Research into Walter Benjamin's theory of the authenticity of the work of art, and in particular his concept of "aura," has helped inform the creation of a marketing strategy propelled by value driven mechanisms found within the Art Market for The Private Collection. Particular emphasis is placed on how brand value drives sales in this thesis. Thus, The Private Collection: Aura, the Cult of Celebrity, and the Construct of Value in Saleable Works of Art, defines The Private Collection as a tailored system built expressly for engagement with economic forces inside the art industry. As a result, the position of this study is based on the marketability of the object through particular driving forces that have seeped into the value system of the saleable work of art. The position of this thesis is that in this commercialist system, driving forces of value can be sustained within instances of the multiple. The project additionally supports this in maintaining that interaction from a fine art perspective would be limited if restricted to orthodox approaches (a gallery showing, and one print works), which is why a more economically interactive approach (e-commerce) was decided on for the exhibition component. The Private Collection offers an observation that the worth of a saleable work of art has become a warped representation of the commercial context we find ourselves in and that value is only awarded through particular kingmakers of the system. The practical component of this submission can be viewed online by clicking the image below. Please note that the website is not optimised for phone or tablet use, please instead view it on a computer (preferably a desktop) in full screen mode.
Keywords: Aura; Celebrities; Consumerism; Art and society; Computer art; AI art; Value